Case Report: Esophagectomy and Azygos Continuation of the Inferior Vena Cava: A Lethal Combination - Zhang, Yan; Ding, Zheng; Mu, Teng; Pan, Xue; Zhang, Guoqing; Li, Xiangnan (Frontiers in Cardiovascular Medicine, 2022)
Azygos continuation of the inferior vena cava (IVC) is rare in the general population and even rarer in patients with esophageal carcinoma. In 90% of the cases, this congenital IVC variant is an isolated variant and does not affect the patient’s growth and development. However, thoracic surgery such as esophagectomy would be fatal if the flow through this connection was interrupted. We present a case of minimally invasive esophagectomy in a patient with azygos continuation of the IVC.